No evidence for lymphatic filariasis transmission in big cities affected by conflict related rural-urban migration in Sierra Leone and Liberia. - Dziedzom K de Souza; Santigie Sesay; Marnijina G Moore; Rashid Ansumana; Charles A Narh; Karsor Kollie; Maria P Rebollo; Benjamin G Koudou; Joseph B Koroma; Fatorma K Bolay; Daniel A Boakye; Moses J Bockarie (PLoS Neglected Tropical Diseases)
Background In West Africa, the principal vectors of lymphatic filariasis (LF) are Anopheles species with Culex species playing only a minor role in transmission, if any. Being a predominantly rural disease, the question remains whether conflict-related migration of rural populations into urban areas would be sufficient for active transmission of the parasite. Methodology/principal findings We examined LF transmission in urban areas in post-conflict Sierra Leone and Liberia that experienced significant rural-urban migration. Mosquitoes from Freetown and Monrovia, were analyzed for infection with Wuchereria bancrofti. We also undertook a transmission assessment survey (TAS) in Bo and Pujehun districts in Sierra Leone. The majority of the mosquitoes collected were Culex species, while Anopheles species were present in low numbers. The mosquitoes were analyzed in pools, with a maximum of 20 mosquitoes per pool. In both countries, a total of 1731 An. gambiae and 14342 Culex were analyzed for W. bancrofti, using the PCR. Two pools of Culex mosquitoes and 1 pool of An. gambiae were found infected from one community in Freetown. Pool screening analysis indicated a maximum likelihood of infection of 0.004 (95% CI of 0.00012-0.021) and 0.015 (95% CI of 0.0018-0.052) for the An. gambiae and Culex respectively. The results indicate that An. gambiae is present in low numbers, with a microfilaria prevalence breaking threshold value not sufficient to maintain transmission. The results of the TAS in Bo and Pujehun also indicated an antigen prevalence of 0.19% and 0.67% in children, respectively. This is well below the recommended 2% level for stopping MDA in Anopheles transmission areas, according to WHO guidelines. Conclusions We found no evidence for active transmission of LF in cities, where internally displaced persons from rural areas lived for many years during the more than 10 years conflict in Sierra Leone and Liberia.